Peran Aparatur Pengawas Internal Pemerintah sebagai pengendali mutu dan penjamin kualitas dalam pencegahan penyalahgunaan wewenang Aparatur Sipil Negara. - Agus Adhy Saputra Saputra (Ilmu Hukum Prima (IHP), 2021)
Law Number 30 Year 2014 about Government Administration, becomes legal basic in governance trough effort to improve good governance to prevent abusive practices of state civil employees. The Law related to Government Regulation of the Number 60 Year 2008 of Government Internal Control System which is base on the idea that the application of the government internal control system is attached throughout the activity, influenced by human resources, and sufficient confidence to support the effectiveness of the implementation of internal control system conducted by government internal control officers (APIP) to prevention of abuse of authority by civil state apparatus The purpose of this research to analyze and interpret the implementation of the APIP as a quality control and quality assurance in prevention of abuse of authority. This paper traces some problems about how the application of government internal control in the prevention of abuse of authority, how the authority and controlling of government internal control in the prevention of abuse of authority, and how the strategy of APIP in the prevention of abuse of authority.To answer this problem, researcher used the juridical normative research methods and methods of empirical juridical research. The result research show that implementation of government internal control system not to realize the increasing role of an effective the government internal control and follow on monitoring by APIP still do not get priority in handling. Therefore, still needed reforms of the legislation to prevention of abuse of authority by the civil state apparatus. The government internal control officers expected not only able to improve and creation of good and clean government to push for a more effective through of controlling processes in accordance with its authority in this legislation but also able to carry out a strategies in prevention of abuse of authority